G02 Variability in depth for national-level swimmers’ freestyle dive starts, push starts and tumble turns - Collings, Fran; Thiel, Marco; Fairhurst, Godred; Ball, Derek (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
The dive start and tumble turn are key skills in freestyle swimming and are the fastest part of a race (Higgs, Pease & Sanders, 2016, J Sports Sci, 35, 995-1003). Consistency in performing them, to a high-level, is crucial when races can be won by <0.1s. Many studies have investigated dives, tumble turns and underwater undulatory swimming performance, however, very few have examined the effect of depth (West et al., 2022, Sports Med Open, 8). Swimming depth will affect wave drag, total distance travelled underwater and, possibly, kick amplitude. Collectively, these will impact dive and tumble turn performance. The current project aims to quantify the variability of a swimmer’s freely chosen depth when performing a freestyle dive start, push start and turn. Ethics approval for this study was provided by the School of Medicine’s Research ethics board. We aim to recruit 14 participants (7=male, 7=female), over the age of 16 and currently competing at a national level in freestyle events. After a 10-min self-determined warm-up, participants are asked to perform three freestyle dives, push starts, and tumble turns in a randomised order. There are three minutes rest between each task and five minutes between three tasks. Each of the nine tasks will be recorded using a custom-built CONTEMPLAS camera system, using 12 cameras filming at 100Hz. Participants are provided with 5-min to complete a self-determined cool-down. Video recordings will be analysed using SIMI Motion capture to perform manual digitisation. A coefficient of variance analysis and a repeated measures Anova and intraclass correlation to quantify the variability in depth within the dives, push starts and the turns at both an individual and group level. As part of this study, we are also assessing the reliability and validity of an automated digitising software package. The validity and reliability of the automatic digitisation method versus the manual digitisation method was analysed via a Bland Altman analysis to obtain the limits of agreement between the two methodologies. The results are pending, although they will be used to assign individual swimmers with target depth ranges for subsequent experiments that aim to identify the optimum depth for these skills.